Fungal communities influence root exudation rates in pine seedlings. Issue 3 (7th November 2012) - Meier, Ina C.; Avis, Peter G.; Phillips, Richard P.
Abstract Root exudates are hypothesized to play a central role in belowground food webs, nutrient turnover, and soil C dynamics in forests, but little is known about the extent to which root‐associated microbial communities influence exudation rates in trees. We used a novel experimental technique to inoculate loblolly pine (Pinus taeda L.) seedlings with indigenous forest fungi to examine how diverse fungal communities influence exudation. Surface‐sterilized seeds were sown in intact, unsieved soil cores for 14 weeks to promote root colonization by fungi. After 14 weeks, we transferred seedlings and root‐associated fungi into cuvettes and measured exudate accumulation in trap solutions. Both the abundance and identity of root‐associated fungi influenced exudation. Exudation rates were greatest in root systems least colonized by ectomycorrhizal (ECM) fungi and most colonized by putative pathogenic and saprotrophic fungi. However, the ECM community composition was not a strong determinant of exudation rates. These results suggest that environmental conditions that influence the degree to which tree roots are colonized by pathogenic and saprotrophic vs. mutualistic fungi are likely to mediate fluxes of labile C in forest soils, with consequences for soil biogeochemistry and ecosystem processes.